Evaluation and taxonomy of agronomically important Striga species - Mohammed, I.B.; Musselman, L.; Aigbokhan, E.I.; Berner, D.K.; Moreno, M.T. (1996)
Taxonomic studies of the taxa clustered about Striga asiatica, S. hermonthica, and S. gesnerioides are presented based on a cladistic study of African plants. The S. asiatica cluster includes S. elegans, S. hirsuta, and S. lutea. Striga asiatica is considered to be derived from a native species near S. elegans. Artificial hybridization indicates a close relationship between S. hermonthica and S. aspera. Several host morphotypes of S. gesnerioides were examined. While each morphotype exhibits features of host specificity, branching, and corolla color, there is little basis for any formal taxonomic recognition.